Improving Access to, Use of, and Outcomes from Public Health Programs: The Importance of Building and Maintaining Trust with Patients/Clients - Ward, Paul Russell (Frontiers in Public Health, 2017)
Abstract The main aim of this paper is to argue for the centrality of ‘trust’ for the development and maintenance of health and wellbeing of individuals, communities and societies. I argue that public health practitioners and policy makers need to take ‘public trust’ seriously if they intend to both improve the public’s health and improve engagement between members of the public and public health systems. Public health practitioners implement a range of services and interventions aimed at improving health, but implicit within this is a requirement for individuals to trust the practitioners and the services/interventions, before they will engage with them. I then go on to provide an overview of the theory of trust within sociology and show why it is important to understand this theory in order to promote trust in public health services. I then draw on literature in three classic areas of public health - hospitals, cancer screening and childhood immunisation - to show why trust is vital in terms of understanding and potentially improving uptake of services. The case studies within this paper reveal that public health practitioners need to understand the centrality of building and maintaining trusting relationships with patients/clients because people who distrust public health services are less likely to use them, less likely to follow advice or recommendations and more likely to have poorer health outcomes.